Computing fluid dynamics on burner air flow in natural draft furnaces - Alabdalah, Asya; Ibrahim, Hassan Al-haj; Aloosh, Ethat (International Journal Of Chemistry, Mathematics And Physics(IJCMP), 2018)
The mean key variable to control the burner performance for safe and efficient operations is the amount of excess air or oxygen which flow to react with fuel. In accordance with Typical Draft Profile in a Natural Draft furnace the numerical results of computing fluid dynamics model of the air flow from the environment to the burner by adjusting the area of air box prototype openings will give the necessary information to adjust the performance of burner as optimum. The model of air box prototype is useful tool in applying similarity theory on another burners̕ designs which depends the air box tools to calibrate the quantity of combustion air flow to the burner.